2021
DOI: 10.1002/er.6661
|View full text |Cite
|
Sign up to set email alerts
|

MicroURANUS : Core design for long‐cycle lead‐bismuth‐cooled fast reactor for marine applications

Abstract: Summary A core design of MicroURANUS, a long‐cycle lead‐bismuth‐cooled fast nuclear reactor for marine applications, is presented. It aims to generate a power of 60MWth, which can be regulated during operation. MicroURANUS was designed to achieve a small burnup reactivity swing for 30 effective full‐power years of a lifetime without refueling. To attain these goals, a unit cell study with uranium oxide fuel was initiated to lay a solid foundation for core design, owing to size constraints. A reflector optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…The major fissile isotope is Pu-239. Furthermore, in the case of MicroURANUS, the production of approximately 465 kg during 30 EFPY was calculated in the core design process (as shown in Figure 1A) (Nguyen et al, 2021). Variations in the thermal conductivity, heat capacity, and thermal expansion of the fuel caused by plutonium generation were considered as variations during operation through the weight fraction and composition of Pu-239, Pu-240, and Pu-241.…”
Section: Pu Generation and Radial Power Profilementioning
confidence: 99%
See 2 more Smart Citations
“…The major fissile isotope is Pu-239. Furthermore, in the case of MicroURANUS, the production of approximately 465 kg during 30 EFPY was calculated in the core design process (as shown in Figure 1A) (Nguyen et al, 2021). Variations in the thermal conductivity, heat capacity, and thermal expansion of the fuel caused by plutonium generation were considered as variations during operation through the weight fraction and composition of Pu-239, Pu-240, and Pu-241.…”
Section: Pu Generation and Radial Power Profilementioning
confidence: 99%
“…In addition to the fuel material properties, the influence of the variations in fuel irradiation behavior caused by plutonium generation was investigated. It is reported that a fission gas release enhancement effect occurs in the case of a MOX with 20 wt% plutonium (which is operated in a fast reactor) it is reported that there is a fission gas release enhancement effect owing to inhomogeneity caused by the segregation of PuO 2 FIGURE 1 (A) Mass variation profiles of U and Pu isotopes and (B) composition profile of plutonium (Nguyen et al, 2021).…”
Section: Pu Generation and Radial Power Profilementioning
confidence: 99%
See 1 more Smart Citation
“…The MicroURANUS power reactor is also a lead-bismuth-cooled fast reactor designed for marine applications. 9 It provides an output power of 60 MWt, of which the core diameter and height are 200 and 155 cm, respectively. Coolant pumps and auxiliary systems can be eliminated by using heat pipe configurations.…”
Section: Introductionmentioning
confidence: 99%
“…Its core diameter and height are 192.2 cm and 100 cm with a weight of 34.86 metric tons. The MicroURANUS power reactor is also a lead‐bismuth‐cooled fast reactor designed for marine applications 9 . It provides an output power of 60 MWt, of which the core diameter and height are 200 and 155 cm, respectively.…”
Section: Introductionmentioning
confidence: 99%